Natural Disaster Governance: Barriers For Turkey - Tolgahan Aydıner; Hüseyin Özgür (European Scientific Journal, ESJ, 2016)
The aim of this study is to analyze the barriers of natural disaster governance for Turkey. First part of the study consists of definitions of disasters and disaster management cycle, theoretical discussions of natural disaster and local governance. The continuing and challenging part gives attention why Turkey has not adopted the natural disaster governance. This part consists of discussions of transcendental state, weak civil society and immaturity of local governance of Turkey. The mentioned discussions aim to correlate those barriers with immaturity of natural disaster governance. The study ends up with general evaluations and conclusions.